Eksistensi Dan Aspek Hukum Penyelenggaraan Waralaba Menurut Hukum Positif Di Indonesia - Darmawan, Monica Virga; Urbanisasi, Urbanisasi (Peneliti.net, 2023)
Franchising is an exclusive right owned and/or granted to someone to be used and utilized by other parties based on a franchise agreement by providing royalties to the owner of the right. Franchising, which is a business method that has its own characteristics, can cause problems. The research method used in this research is normative juridical. The normative juridical research method is a library legal research conducted by examining library materials or secondary data only, the purpose of the writing is to read the understanding of the existence of the legal aspects of franchising, the results of the writing Franchising is the exclusive right of a person or entrepreneur to a commercial business system to market goods and / or services that have proven successful and can be utilized and / or used by other parties based on a franchise agreement.